2001
DOI: 10.1007/bf02345289
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of transfer function estimates in cardiovascular variability analysis

Abstract: Transfer function (TF) analysis is a widely diffused technique in the assessment of the relationship between short-term cardiovascular variability signals, particularly blood pressure, heart rate and respiration. To guarantee the reliability of the estimates, a conventional threshold of 0.5 on the magnitude squared coherence (MSC) is commonly used, although (i) other analysis parameters play a role and (ii) lower values of MSC are frequently unavoidable in physiological systems. In this study, computer simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
84
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(89 citation statements)
references
References 13 publications
4
84
0
1
Order By: Relevance
“…This approach is equivalent to setting the threshold at zero. This approach produces phase and gain estimates that are comparable with those obtained under conditions of high coherence (e.g., during cyclic squat-to-stand exercise) (8,53), presumably because averaging filters out the random variability of the function around its true value (38).…”
Section: Derivation Of Transfer Function Gain and Phasementioning
confidence: 85%
“…This approach is equivalent to setting the threshold at zero. This approach produces phase and gain estimates that are comparable with those obtained under conditions of high coherence (e.g., during cyclic squat-to-stand exercise) (8,53), presumably because averaging filters out the random variability of the function around its true value (38).…”
Section: Derivation Of Transfer Function Gain and Phasementioning
confidence: 85%
“…Recently, however, this approach has been criticized on the grounds that (i) the reliability of the estimates depends on other parameters besides the coherence and (ii) low values of coherence are unavoidable in physiological systems owing to an impaired baroreflex brought about by a pathological condition and/or a low signal-to-noise ratio in the signals. 23 Indeed, it has been shown that the measurability of BRS with the Robbe method in post-MI, chronic heart failure and geriatric patients the measurability is as low as <50%. 15,24 In the present study this index could be measured in 65 of 112 patients (58%).…”
Section: Discussionmentioning
confidence: 99%
“…BRS was determined from spontaneous fluctuations in the RR interval and SBP during the 15 and 6 breaths per minute recordings using the sequence method (BRS+/+, BRS−/−) [34], the alpha coefficient (Alpha low-frequency BRS) [35] and the transfer function technique (TF-BRS) [36]. In the sequence method, BRS was estimated by identifying spontaneously occurring sequences of three or more consecutive heartbeats in which both SBP and the subsequent RR intervals changed in the same direction.…”
Section: Study Populationmentioning
confidence: 99%